2017
DOI: 10.1080/02656736.2017.1289252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capacitive and Resistive electric transfer on haemoglobin saturation and tissue temperature

Abstract: The effect on haemoglobin saturation was higher in the CRet group than in the HP group. In addition, the CRet intervention warmed deep tissue more effectively than HP intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(111 citation statements)
references
References 30 publications
(29 reference statements)
0
109
0
2
Order By: Relevance
“…The main underlying mechanism is considered to be the rise in temperature associated with electromagnetic energy, which triggers oscillation and friction forces of charged molecules, such as proteins and ions. This increase in temperature has been described at a superficial level (10-15 mm, which is believed to reflect the state of the subcutaneous adipose tissue and fascia), but also at a deeper level (20-30 mm, which is supposed to reflect the state of the muscle layer) [7,8,13]. The mild elevation of the temperature achieved in these studies was enough to accelerate metabolic activity and to improve local circulation.…”
Section: Changes In Energetic Parametersmentioning
confidence: 53%
See 2 more Smart Citations
“…The main underlying mechanism is considered to be the rise in temperature associated with electromagnetic energy, which triggers oscillation and friction forces of charged molecules, such as proteins and ions. This increase in temperature has been described at a superficial level (10-15 mm, which is believed to reflect the state of the subcutaneous adipose tissue and fascia), but also at a deeper level (20-30 mm, which is supposed to reflect the state of the muscle layer) [7,8,13]. The mild elevation of the temperature achieved in these studies was enough to accelerate metabolic activity and to improve local circulation.…”
Section: Changes In Energetic Parametersmentioning
confidence: 53%
“…In addition, a summing effect appeared to happen in the second session of CRET in these parameters, since SL was longer on the second day (26, 30 and 36 h after the first session) compared to the first day (2, 6 and 12 h). The duration of the increased temperature and other physiological effects caused by CRET have not been defined exactly, and skin, superficial and deep temperature, blood flow and hemoglobin saturation, have been measured up to only to 30 min post-application [7,8,13]. Moreover, several in vitro studies have shown that CRET application also exerts non-thermal effects, consisting of a modulation of cellular activity and changes in membrane transport [18,19].…”
Section: Changes In Stride Spatiotemporal Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, although CARE therapy is delivered in a static mode, it has a substantial muscle-relaxing effect, which facilitates shoulder rehabilitative exercises. 5,6 In particular, the use of static electrodes avoids the bias caused by differences in operator skill and training. The massage that the therapist performs with the hand piece in classical diathermy renders the treatment operator-dependent, which may cause bias.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Bito et al 4 reported that CARE substantially improves blood circulation in the peritendinous region and increases haemoglobin saturation. In addition, CARE therapy warms deep tissue; 5 the resulting greater vascularization promotes the relaxation of tissues (especially muscular tissue) and drainage of swelling (oedema and haematoma).…”
Section: Introductionmentioning
confidence: 99%